IMPLEMENTASI PENDEKATAN DEEP LEARNING PADA MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) SMA NEGERI 02 REBANG TANGKAS WAY KANAN - Azis Rahmadan; Lungit Wicaksono; Alifia Ramadhina Putri; Joan Siswoyo (STKIP Subang, 2026)
This study describes the implementation of the deep learning approach in Physical Education, Sports, and Health (PJOK) subjects at SMA Negeri 2 Rebang Tangkas using a qualitative descriptive method with a purposive sampling technique involving the principal, curriculum vice principal, infrastructure vice principal, PJOK teacher, homeroom teacher, and 14 students. Data collection techniques used observation, interviews, and documentation, then data analysis techniques used reduction, presentation, and verification. The results of the study show, (1) Deep learning-based PJOK learning at SMA Negeri 2 Rebang Tangkas aims to create meaningful learning experiences, prioritizing understanding of concepts and values, in addition to physical skills. Planning includes objectives, flows, and modules that are tailored to students' conditions and needs. (2) The implementation of learning prioritizes three principles, namely mindful, Meaning, and joy, by actively involving students in activities that connect the material to everyday life. (3) Evaluation of deep learning-based learning includes a comprehensive assessment of students' knowledge, attitudes, and skills, using tests, non-tests, as well as diagnostic, formative, and summative assessments to measure progress and adjust learning. However, its implementation still faces obstacles such as limited facilities and infrastructure, differences in student abilities, weather conditions, and teacher preparedness. The conclusion of this study is that the deep learning approach can increase active engagement, in-depth understanding, and internalization of values, but requires strengthening consistency in implementation and utilization of learning media to create an effective, contextual, and sustainable PJOK learning experience.